2021
DOI: 10.1002/pc.26116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of POSS nanoparticles on the microstructure and mechanical properties of carbon fiber reinforced epoxy hybrid composites

Abstract: The possibility to design composites with superior properties by incorporation of nanoscale reinforcing material still remains to be fulfilled. In the current study, bisphenol A diglycidyl ether-based epoxy resin has been successfully modified with polyhedral oligomeric silsesquioxane (POSS) nanoparticles to give epoxy/POSS nanocomposites. Carbon fiber reinforced composites with different fiber orientations are processed via vacuum bagging technique using this composite as the matrix. Scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The inclusion of POSS nanofillers in the polymer matrix has promoted significant improvements in the mechanical properties of the carbon fiber (CF) reinforced composites compared to the original composites. [33] Octaglycidyl polyhedral oligomeric silsesquioxane (gly-POSS) was successfully grafted on CFs surface to enhance interfacial properties and impact toughness of CFs reinforced methylphenylsilicone resin (MPSR) composites. [34] Although there has been remarkable progress in healing composites over the past decade, the technology to healing damage of matrix and interface synchronously presents challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of POSS nanofillers in the polymer matrix has promoted significant improvements in the mechanical properties of the carbon fiber (CF) reinforced composites compared to the original composites. [33] Octaglycidyl polyhedral oligomeric silsesquioxane (gly-POSS) was successfully grafted on CFs surface to enhance interfacial properties and impact toughness of CFs reinforced methylphenylsilicone resin (MPSR) composites. [34] Although there has been remarkable progress in healing composites over the past decade, the technology to healing damage of matrix and interface synchronously presents challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Chang and coworkers [ 8 ] demonstrated that amorphous carbon as an intermediate layer between CFs and the sponge was essential to enhance the mechanical strength and toughness of the material interface. Kurtulus et al [ 9 ] incorporated polyhedral oligomeric silsesquioxane nanoparticles as heterogeneous layer to design CF‐reinforced epoxy (EP) composites (CFRPs) with superior properties. Although heterogeneous layer has a significant impact on improving the functions and properties of the formed composites, the influences of grafted components of both rigid and flexible parts that make up the interface layer on the structure and properties of the composite interface have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This study intends to assess the structural performance and applicability of hybrid polymer composites for pick-and-place robot grippers, automobile and aerospace structures used in critical situations (Harries, 2014). Specifically, in critical infrastructure pick-and-place robot grippers, the structural performance of hybrid polymer composites is assessed using the quasi-static sequence approach, which is a specialized technique to enhance mechanical characteristics of the composite structures (Wondu and Kim, 2023;Kurtulus et al, 2021). This quasi-static sequence method enables a complete understanding of how these composites perform under various loading scenarios, thereby providing essential knowledge for designing and fabricating critical infrastructure pick-and-place robot grippers, automobile and aerospace structures (Portico et al, 2021).…”
Section: Introductionmentioning
confidence: 99%